2019
DOI: 10.7759/cureus.5036
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of an Acute Care Surgical Service on the Quality and Efficiency of Care Outcome Indicators for Patients with General Surgical Emergencies

Abstract: Background Acute care surgery (ACS) models address high volumes of emergency general surgery and emergency room (ER) overcrowding. The impact of ACS service model implementation on the quality and efficiency of care (EOC) outcomes in acute appendicitis (AA) and acute cholecystitis (AC) cohorts was evaluated. Methods A retrospective chart review (N=1,229) of adult AA and AC patients admitted prior to (pre-ACS; n=507; three hospitals; 2007) and after regionalization (R-ACS; n=722… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Even if surgeons believe that surgery should be delayed, almost half of the elective cholecystectomy procedures are carried out after 3 months [ 31 , 49 ]. So, performing cholecystectomy during the same admission, using an acute care surgery model, would considerably decrease the elective burden [ 22 , 67 ]. There is no local expertise for laparoscopic common bile duct exploration (LCBDE).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if surgeons believe that surgery should be delayed, almost half of the elective cholecystectomy procedures are carried out after 3 months [ 31 , 49 ]. So, performing cholecystectomy during the same admission, using an acute care surgery model, would considerably decrease the elective burden [ 22 , 67 ]. There is no local expertise for laparoscopic common bile duct exploration (LCBDE).…”
Section: Discussionmentioning
confidence: 99%
“…A coordinated fast track investigation and treatment, with a dedicated team and institutional commitment towards fulfillment of guidelines remains mandatory [ 72 ]. Also, continuous and rigorous evaluation in the quality of care and compliance with guidelines should be implemented [ 34 , 67 , 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of resources, particularly the availability of the operating room during the daytime, 11 , 54 and competition with busy elective practices 11 are, like others, 1 , 41 , 50 additional reasons to delay surgery. Implementing an acute care surgery model with dedicated operative time would be a solution to partially alleviate this problem, 11 , 55 although surgeons remain reluctant to perform cholecystectomy at night. We have found that patients are rarely opposed to undergoing cholecystectomy during the same admission, except sometimes older adults.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of nursing care in the operating room will directly affect the operation of the entire surgical system [17] . Health care systems around the world are facing the challenge of improving the quality of care and reducing the risk of adverse events [18,19] .…”
Section: Intraoperative Carementioning
confidence: 99%